2010
DOI: 10.1117/12.845595
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in multiresolution analysis of 3D meshes and their applications

Abstract: 3D meshes are widely used in computer graphics applications for approximating 3D models. When representing complex shapes in raw data format, meshes consume a large amount of space. Applications calling for compact and fast processing of large 3D meshes have motivated a multitude of algorithms developped to process these datasets efficiently. The concept of multiresolution analysis proposes an efficient and versatile tool for digital geometric processing allowing for numerous applications. In this paper, we su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…However they introduced a new irregular subdivision scheme and a complex simplification technique in order to define surface patches suitable for the irregular meshes [38]. A review of recent advances in multiresolution analysis for 3D meshes can be found in [39].…”
Section: -Multi-scales Analysis On Surfaces Represented By Triangulamentioning
confidence: 99%
“…However they introduced a new irregular subdivision scheme and a complex simplification technique in order to define surface patches suitable for the irregular meshes [38]. A review of recent advances in multiresolution analysis for 3D meshes can be found in [39].…”
Section: -Multi-scales Analysis On Surfaces Represented By Triangulamentioning
confidence: 99%